Explicit aerosol–cloud interactions in the Dutch Atmospheric Large-Eddy Simulation model DALES4.1-M7 - M. de Bruine; M. de Bruine; M. Krol; M. Krol; J. Vilà-Guerau de Arellano; T. Röckmann (Geoscientific Model Development, 2019)
Large-eddy simulation (LES) models are an excellent tool to improve our understanding of aerosol–cloud interactions (ACI). We introduce a prognostic aerosol scheme with multiple aerosol species in the Dutch Atmospheric Large-Eddy Simulation model (DALES), especially focused on simulating the impact of cloud microphysical processes on the aerosol population. The numerical treatment of aerosol activation is a crucial element for simulating both cloud and aerosol characteristics. Two methods are implemented and discussed: an explicit activation scheme based on κ-Köhler theory and a more classic approach using updraught strength. Sample model simulations are based on the Rain in Shallow Cumulus over the Ocean (RICO) campaign, characterized by rapidly precipitating warm-phase shallow cumulus clouds. We find that in this pristine ocean environment virtually all aerosol mass in cloud droplets is the result of the activation process, while in-cloud scavenging is relatively inefficient. Despite the rapid formation of precipitation, most of the in-cloud aerosol mass is returned to the atmosphere by cloud evaporation. The strength of aerosol processing through subsequent cloud cycles is found to be particularly sensitive to the activation scheme and resulting cloud characteristics. However, the precipitation processes are considerably less sensitive. Scavenging by precipitation is the dominant source for in-rain aerosol mass. About half of the in-rain aerosol reaches the surface, while the rest is released by evaporation of falling precipitation. The effect of cloud microphysics on the average aerosol size depends on the balance between the evaporation of clouds and rain and ultimate removal by precipitation. Analysis of typical aerosol size associated with the different microphysical processes shows that aerosols resuspended by cloud evaporation have a radius that is only 5 % to 10 % larger than the originally activated aerosols. In contrast, aerosols released by evaporating precipitation are an order of magnitude larger.